Cucujus tulliae sp. n. – an endemic Mediterranean saproxylic beetle from genus Cucujus Fabricius, 1775 (Coleoptera, Cucujidae), and keys for identification of adults and larvae native to Europe - Bonacci, Teresa (Pensoft Publishers, 2012)

(untitled)
Abstract. Cucujus tulliae sp. n. is described as a new member of genus Cucujus Fabricius, 1775 (Coleoptera, Cucujidae), which enumerates at present eleven species distributed in Eurasia and northern America. This saproxylic beetle is the first Cucujus species known only from Mediterranean and it is probably endemic to Calabria (Italy). The species was found especially in old–growth mountain forests of high conservation value (i.e. national parks) dominated by Calabrian pine (Pinus laricio calabrica). We hypothesize that Cucujus tulliae sp. n. probably evolved from isolated populations of Cucujus haematodes Erichson, 1845. The species is thus relictual and of high conservation value, corresponding at least to endangered (EN) category with respect to recent IUCN criterion. Cucujus tulliae sp. n. is here compared with two species native to Europe – Cucujus haematodes and Cucujus cinnaberinus (Scopoli, 1763) and with the Caucasian Cucujus haematodes caucasicus Motschulsky, 1845, which is confirmed as a valid subspecies. The male genitalia of this Caucasian form have been examined and illustrated for the first time. A comprehensive key to adults and larvae of European species is provided.